EXTH-36. ELECTROCONVULSIVE SEIZURE-INDUCED CHANGES IN THE TUMOR MICROENVIRONMENT PROMOTE SURVIVAL IN GLIOMA-BEARING MICE. (12th November 2021) - Sita, Timothy; Hurley, Lisa; Drumm, Michael; Tommasini-Ghelfi, Serena; Mahajan, Akanksha; Dussold, Corey; Murnan, Kevin; Sachdev, Sean; Horbinski, Craig; Stupp, Roger; Stegh, Alexander
Abstract: PURPOSE: Growing evidence indicates that the neurotransmitters dysregulated in psychiatric disorders are similarly dysregulated in glioblastoma (GBM) biology. GBM cells are dependent on bountiful neuronal glutamate, utilize elevated dopamine receptor expression to augment progression, and catabolize serotonin to drive proliferation and inhibit anti-tumor immunity. The clinical induction of seizure, known as electroconvulsive therapy (ECT), has been used by psychiatrists since the 1930s to correct these dysregulations and can additionally improve medication blood-brain barrier (BBB) penetrance. We hypothesized that seizure-induced changes in the glioma microenvironment occur with ECT, slowing tumor progression, increasing BBB permeability, and prolonging overall survival in glioma-bearing mice. METHODS: C57BL6 mice were orthotopically injected with CT-2A-Luc mouse glioma cells. Mice were randomized to receive ECT via ear-clip electrodes or sham treatment daily up to five times per week. Intracranial progression was monitored via bioluminescent signal from CT-2A-Luc xenografts. BBB permeability was assessed by subjecting mice to ECT or sham treatment immediately following intravenous injection of sodium fluorescein. RESULTS: Intracranial progression was maximally reduced in ECT-treated mice relative to sham-treated mice after 17 ECT treatments (ECT radiance 2.6 x 10 9 photons/second versus sham 4.7 x 10 9 photons/second, p=0.013), which was further confirmed by both decreased tumor weight and tumor size on histologic evaluation. This translated into an improvement in overall survival from median 29 days in sham-treated mice to 38 days in ECT-treated mice (p=0.0018). Mean seizure duration was 41.8 seconds and positively correlated with overall survival (Pearson coefficient r=0.63, p=0.028). Brain parenchymal uptake of sodium fluorescein was significantly higher in ECT-treated mice (mean relative increase in ECS to sham radiance of 1.47, p< 0.05). CONCLUSION: Repeated ECT slows tumor progression and prolongs overall survival in C57BL6 mice bearing CT-2A-Luc xenografts. The BBB is compromised immediately following ECT. ECT merits further oncologic investigation as a potential therapeutic in GBM.